Current and future therapeutic options for chronic hepatitis D virus infection - Mariantonietta Pisaturo; Antonio Russo; Pierantonio Grimaldi; Salvatore Martini; Nicola Coppola (Frontiers in Cellular and Infection Microbiology)
In the last few years there have been innovations in HDV therapy which have brought new excitement in the scientific community also considering the few therapeutic opportunities. Recently, new molecular targets have been identified, both in monotherapy and in combination with peginterferon alpha (PegIFNα). Evaluating this review of the literature of the last ten years, HDV-related chronic hepatitis seems to have become a potentially curable disease, a statement that was unthinkable a few years ago. There are old and new weapons at our disposal. The old weapons are PegIFNα and recently PegIFN-lambda (PegIFNλ). PegIFNα, for which there are more data, appears to be an excellent combination regimen, if not contraindicated, both for Bulevirtide (BLV), data supported by important clinical trials and real-world studies, and probably for lonarfanib, although in the latter case the results are not yet definitive as the studies are fewer. However, data on long-term follow-up are needed.